ҚУРЫЛЫС БАҒДАРЫНДА ИННОВАЦИЯЛЫҚ ОҚЫТЫЎ - Ешниязов, Р. (SCIENCE and SOCIETY, 2022)
Successful interdisciplinary team work within construction processes requires a wide range of competences and skills. This article discusses the integration of these capabilities into the education of civil engineers. The main attention was paid to the development of competencies and technical knowledge based on projects.